Complex analysis and algebraic geometry : a volume in memory of Michael Schneider - Peternell, Th. (Thomas), 1954-; Schreyer, Frank-Olaf (Proceedings in mathematics., 2016)
The series is aimed specifically at publishing peer reviewed reviews and contributions presented at workshops and conferences. Each volume is associated with a particular conference, symposium or workshop. These events cover various topics within pure and applied mathematics and provide up-to-date coverage of new developments, methods and applications.